Adapting to change: Empowering MSMEs in Tasik Said Naum Market through digital marketing strategies - Rahma Nur Praptiwi; M. Jamal Al Bakrie; Iftita Rahmi; Innas Rovino Katuruni; Anita Rahmawati (Community Empowerment, 2024)
Another effect of the pandemic is a shift in people's shopping habits over time. Nowadays, people prefer to shop online due to its practicality and often lower prices. This trend has led to complaints from Micro, Small, and Medium Enterprises (MSMEs) players at Tasik Tanah Abang Market, citing continuous declines in sales. Increasing sales and income requires knowledge and understanding that align with the needs and challenges faced by traders at Tasik Said Na'um Market. The goal is to equip traders to compete in the digital market post-pandemic. The implementation of these community service activities includes Focus Group Discussions (FGD) and education on basic marketing concepts. The results of the activities undertaken include an improved understanding of problems and potential solutions for traders, along with increased knowledge about digital marketing. The required digital marketing skills include sales assistance through live selling, providing traders with a better understanding of how to utilize live selling platforms effectively to market their products.